Nieposłuszeństwo obywatelskie a państwo demokratyczne - Gadkowski, Aleksander; Różański, Krzysztof; Sokołowski, Łukasz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The aim of this article is to present the complex issue of civil disobedience in the democratic state. The authors pay attention to the fact that ineffectiveness may lay the foundation for civil disobedience. It should be stressed that the activity of the citizens in the form of civil disobedience shall not always harmonize with the legal norms of applicable democratic state of law. Civil disobedience may reflect varied interests of different social groups. These points of view – often very different - shall be perceived by the governmental authority, which in the decision-making process is forced to choose between the so-called “lesser evil”. The authors present the issue of civil disobedience by showing examples from the country and abroad.